Assessment conceptions of preservice and inservice teachers: implications for the quality of educational research and social responsibility - Tammaro, Rosanna; Gragnaniello, Deborah (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
This study looks at how teachers, both those training to become teachers and those already teaching, think about teaching in the modern educational situation. In this situation, the way teachers teach different subjects and the way they teach subjects that don’t fall into just one subject area are both very important. This research-education aims to bridge the gap between academic theory and its practical application. It does this by looking at how teachers’ beliefs affect their teaching (Thompson, 1992). To do this, a questionnaire (Brown et al., 2019) was given to 387 teachers who were already teaching, and 163 teachers who were training to be teachers. The teachers were asked questions about what they thought about the different teaching methods. The results show that new teachers are aware of how they are doing in their training and how others are assessing them. However, in-service teachers, while still focusing on improvement, show a greater emphasis on the roles of institutions and individuals. This suggests that practical experience and theoretical principles work well together, and that certification functions are a natural result. These differences show how important it is to keep learning to balance different ways of assessing things and using academic knowledge in real-life situations. In conclusion, comparing how the two groups think about teaching can help improve how teachers are trained and get universities and schools working together more. This can help make the education system fairer and more effective (Rosa & Ciani, 2023; Scierri, 2024).